2003
DOI: 10.1093/jb/mvg126
|View full text |Cite
|
Sign up to set email alerts
|

A Temperature-Sensitive Mutant of the Mammalian RNA Helicase, DEAD-BOX X Isoform, DBX, Defective in the Transition from G1 to S Phase

Abstract: ts ET24 cells are a novel temperature-sensitive (ts) mutant for cell proliferation of hamster BHK21 cells. The human genomic DNA which rescued the temperature-sensitive lethality of ts ET24 cells was isolated and screened for an open reading frame in the deposited human genomic library. X chromosomal DBX gene encoding the RNA helicase, DEAD-BOX X isoform, which is homologous to yeast Ded1p, was found to be defective in this mutant. The single point mutation (P267S) was localized between the Motifs I and Ia of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 22 publications
8
33
0
Order By: Relevance
“…An earlier report shows that total protein synthesis in a mouse BHK21-derived cell line harboring a temperature-sensitive DDX3 mutation appears to be normal even at the non-permissive temperature. 29 In line with this result, we also observed that knockdown of DDX3 by RNA interference yielded no significant effect on global protein synthesis. 18 These data thus raise a possibility that DDX3 does not play a key role in bulk translation.…”
Section: Role Of the Mammalian Ddx3 In Translational Controlsupporting
confidence: 78%
“…An earlier report shows that total protein synthesis in a mouse BHK21-derived cell line harboring a temperature-sensitive DDX3 mutation appears to be normal even at the non-permissive temperature. 29 In line with this result, we also observed that knockdown of DDX3 by RNA interference yielded no significant effect on global protein synthesis. 18 These data thus raise a possibility that DDX3 does not play a key role in bulk translation.…”
Section: Role Of the Mammalian Ddx3 In Translational Controlsupporting
confidence: 78%
“…Several lines of evidence have suggested that DDX3 is involved in cell viability (5,12,16,22,27,41), but its underlying molecular mechanism remains elusive. To address this issue, we knocked down DDX3 expression in HeLa cells by using the shRNA strategy.…”
Section: Resultsmentioning
confidence: 99%
“…H1299 and A549 cells were cultured in Dulbecco's modified Eagle's medium (DMEM; Gibco), and U2OS cells were cultured in McCoy's 5A medium (Gibco) at 37°C; both media were supplemented with 10% fetal bovine serum (FBS). Hamster tsET24 cells were kindly given by Takeshi Sekiguchi (Kyushu, Japan) and were cultured essentially the same as HeLa cells, except that tsET24 cells were maintained in 10% CO 2 and at 33.5°C (12). To induce the temperaturesensitive (TS) phenotype, tsET24 cells were shifted to 39.5°C (12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Hamster tsET24 cells, which are temperature sensitive cells with a point mutation in DDX3 (P267S), exhibit G1 arrest at the non-permissive temperature [34]. The residues phosphorylated by cdc2, most importantly Thr204, sit within conserved helicase motifs of DDX3 and are therefore likely to disrupt substrate binding and helicase activity [33,35].…”
Section: Tumour Suppressor Function Of Ddx3mentioning
confidence: 99%